Intermediate Jacobians and the slice filtration - Park, Doosung (MATHEMATICA SCANDINAVICA, 2022)
For every $n$-dimensional smooth projective variety $X$ over ℂ, the motive $M(X)$ is expected to admit a Chow-Künneth decomposition $M_0(X)\oplus … \oplus M_{2n}(X)$. Inspired by the slice filtration of $M(X)$ we propose the definitions of $M_2(X)$ and $M_{2n-2}(X)$. In our construction we use intermediate Jacobians.